Microbial Assimilation of Hydrocarbons: Identification of Phospholipids - Makula, R. A. (1970)
The distribution of phospholipids derived from Micrococcus cerificans was determined under a variety of nutritive conditions. Cells were grown with hexadecane, heptadecane, or acetate serving as the sole carbon source. Total lipid was isolated by chloroform-methanol extraction, and the phospholipid fraction was isolated by silicic acid column chromatography. The phospholipids were characterized by silicic acid chromatography, by thin-layer chromatography, and by identification of water-soluble products resulting from acid hydrolysis of purified phospholipids. Major phospholipids characterized were phosphatidylethanolamine, phosphatidylglycerol, and cardiolipin. Minor phospholipids were phosphatidylglycerol phosphate and phosphatidylserine. Trace amounts of methylated derivatives of phosphatidylethanolamine were determined by incorporation of (14)C from (14)C-methylmethionine. These experiments demonstrated the presence of phosphatidyl-N-methylethanolamine, phosphatidyl-N,N′-dimethylethanolamine, and phosphatidylcholine in trace quantities. Pulse labeling with (14)C-serine demonstrated the direct incorporation of serine into phosphatidylserine followed by decarboxylation to phosphatidylethanolamine.